Cultivating Upper Secondary Students' Mathematical Reasoning-Ability and Attitude towards Mathematics Through Problem-Based Learning - E. Elvis Napitupulu; Didi Suryadi; Yaya S. Kusumah (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2016)
This paper reports some results of a research attempted to cultivate students' mathematical reasoning ability (MRA) by means of implementing problem-based learning (PBL) model. The population was upper secondary students of public schools in Bandung. Cluster sampling technique applied to take sample of amount 158 students from middle-level schools. Data were teachers' assessment on students’ performance in last two months, prior mathematical knowledge (PMK) and MRA test, observations, and interview. Two-factors ANOVA then used to analyze the data. Findings showed that overall students in PBL-classroom achieved better MRA than their counterparts in conventional one though the category in both classrooms was low. Interaction between PBL and PMK factor towards MRA did not emerge. Most part of the participants viewed PBL neither positive nor negative. On the contrary, they assessed that the tasks given made and demanded them thinking and learning more actively than ever. The findings showed adopting PBL in schools to facilitate students getting their higher order thinking skills is a reasonable choice, especially schools having middle or high ability students.Keywords: problem-based learning (PBL), mathematical reasoning ability